1959
DOI: 10.4098/at.arch.59-1
|View full text |Cite
|
Sign up to set email alerts
|

Beobachtungen über den Rumpfabschnitt der Wirbelsäule des Elches - Alces alces L.

Abstract: Beobachtungen über den Rumpfabschnitt der Wirbelsäule des Elches-A lces alces L. Obserwacje nad tułowiowym odcinkiem kręgosłupa łosia-Alces alces L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
1973
1973

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vokken (1961) draw s a tte n tio n to the fact th a t in dom estic cattle (in 1.6% of cases) and sheep (in as m any as 3.5% of cases) deviation can be observed from the norm al num ber of 13 pairs of ribs. Pilarski & Roskosz (1959) observed thoracalisation, lum balisation and sacralisation in th e elk. These sam e authors observed u n ilateral m etam orphosis of the arched rib into th e floating rib in one individual of this species.…”
Section: Discussionmentioning
confidence: 89%
“…Vokken (1961) draw s a tte n tio n to the fact th a t in dom estic cattle (in 1.6% of cases) and sheep (in as m any as 3.5% of cases) deviation can be observed from the norm al num ber of 13 pairs of ribs. Pilarski & Roskosz (1959) observed thoracalisation, lum balisation and sacralisation in th e elk. These sam e authors observed u n ilateral m etam orphosis of the arched rib into th e floating rib in one individual of this species.…”
Section: Discussionmentioning
confidence: 89%
“…All papers (except nos. 31,32,38) has been published in polish with russian, and English, french or german summaries.…”
Section: Polish Theriological Laboratoriesmentioning
confidence: 99%